Price Analysis of Dendrobium Orchid Flowers: Study on Orchid Entrepreneurs in Surabaya - Wanto, Hary (LifeSciFi, 2021)
The economic crisis that caused many companies to close, but on the other hand that the agricultural sector is able to survive when the crisis occurs, the factor from within the orchid is the genetic factor or type of orchid, including natural or cruciferous orchids. If the type of natural orchid then the growth and flowering will be relatively very long if without special treatment, but if the type of orchid cruciferous like Dendrobium then the growth and flowering is relatively faster. To know the production elasticity of Dendrobium orchids of various age ranges in Kayoon Market, Surabaya City is technically efficient. To know the production and price of Dendrobium Orchid Flower in various age range in Kayoon Market, Surabaya City. As information for Orchid Flower entrepreneurs in overcoming problems in problems in orchid business. Orchids belong to the orchid tribe or family